Immunologic aspects of asthma: from molecular mechanisms to disease pathophysiology and clinical translation - Xie, Cong; Yang, Jingyan; Gul, Aman; Li, Yifan; Zhang, Rui; Yalikun, Maimaititusun; Lv, Xiaotong; Lin, Yuhan; Luo, Qingli; Gao, Huijuan (Frontiers in Immunology, 2024)
In the present review, we focused on recent translational and clinical discoveries in asthma immunology, facilitating phenotyping and stratified or personalized interventions for patients with this condition. The immune processes behind chronic inflammation in asthma exhibit marked heterogeneity, with diverse phenotypes defining discernible features and endotypes illuminating the underlying molecular mechanisms. In particular, two primary endotypes of asthma have been identified: "type 2-high," characterized by increased eosinophil levels in the airways and sputum of patients, and "type 2-low," distinguished by increased neutrophils or a pauci-granulocytic profile.Our review encompasses significant advances in both innate and adaptive immunities, with emphasis on the key cellular and molecular mediators, and delves into innovative biological and targeted therapies for all the asthma endotypes. Recognizing that the immunopathology of asthma is dynamic and continuous, exhibiting spatial and temporal variabilities, is the central theme of this review. This complexity is underscored through the innumerable interactions involved, rather than being driven by a single predominant factor. Integrated efforts to improve our understanding of the pathophysiological characteristics of asthma indicate a trend toward an approach based on disease biology, encompassing the combined examination of the clinical, cellular, and molecular dimensions of the disease to more accurately correlate clinical traits with specific disease mechanisms.